Autoimmune Neutropenia Associated With HHV-6 Virus Infection: A Case Report - Kobi Faierstein; Kobi Faierstein; Noya Shilo; Noya Shilo; Asaf Levartovsky; Asaf Levartovsky; Roy Raphael; Roy Raphael; Amir Givon; Amir Givon; Nancy Agmon-Levin; Nancy Agmon-Levin; et al. (Frontiers in Immunology, 2022)
BackgroundAutoimmune neutropenia (AIN) is divided into primary and secondary forms. The former is more prevalent in children and is usually a self-limiting disease. Secondary AIN is more common in adults and often occurs in the setting of another autoimmune disorder or secondary to infections, malignancies or medications. Several viral and bacterial pathogens were described to trigger AIN. Here we report a case of AIN in an adult woman associated with human herpesvirus-6 (HHV-6) infection.Case PresentationWe report a case of AIN in an adult woman associated with HHV-6 infection. The patient presented to the emergency department with fever and painful genital ulcers. Upon arrival, her laboratory workup demonstrated severe neutropenia and elevated inflammatory markers. She was hospitalized and underwent a thorough infectious, hematological, autoimmune and inflammatory workup. Malignancy was also excluded using an advanced whole body radiological scan. Serological tests confirmed the presence of both acute and chronic types of HHV-6 antibodies, at very high titers. Polymerase chain reaction demonstrated a numerous copies of the virus in the patient’s blood. Specific immunofluorescence test confirmed the diagnosis of autoimmune neutropenia.ConclusionSecondary AIN is a rare disease that may affect all range of ages. The adult type is a challenging disorder that has different etiologies and may be triggered by a variable infectious pathogen. The finding of HHV-6 as a possible culprit pathogen may warrant physicians into widening the evaluation and include HHV-6 in the analysis.